Modeling Purchase Intentions of Gen Z in E-Marketplace: An Empirical Investigation in Vietnam - Hoai, Ao Thu; Nga, Duong Quynh; My, Dang Van (Journal of Posthumanism, 2025)
This research investigates how various factors influence Generation Z’s intention to make purchases on e-marketplaces in Vietnam. Based on the theory of reasoned action (TRA) and the technology acceptance model (TAM), the study proposes a conceptual model relating to the latest research in this area. The proposed model was validated through survey data gathered from 600 Generation Z individuals in Vietnam who have yet to purchase in an e-marketplace. The collected data was used to perform structural equations modeling to validate the model. The study evaluates eight proposed factors impacting Generation Z’s purchase intention using SEM techniques: (1) Subjective Norms, (2) Visibility, (3) Trust, (4) Perceived Risk, (5) Enjoyment, (6) Self-Efficacy, (7) Perceived Usefulness, and (8) Perceived Ease of Use. The findings contribute to refining the online shopping scale for Generation Z in Vietnam and provide empirical support for the TRA and the TAM. Additionally, the study offers management implications to assist e-marketplace providers and marketers in developing effective strategies and enhancing their services and offerings.